The IMMENSE Study: The Interplay Between iMMune and ENdothelial Cells in Mediating Cardiovascular Risk in Systemic Lupus Erythematosus - Bortoluzzi, Alessandra; Chighizola, Cecilia Beatrice; Fredi, Micaela; Raschi, Elena; Bodio, Caterina; Privitera, Daniela; Gonelli, Arianna; Silvagni, Ettore; Govoni, Marcello; Cavazzana, Ilaria; Airò, Paolo; Meroni, Pier Luigi; et al. (Frontiers in Immunology, 2020)
Patients with systemic lupus erythematosus (SLE) have a significant increase in cardiovascular risk although they display a preserved number of circulating angiogenic CD3+CD31+CXCR4+ T cells (Tang), a subpopulation of T cells which promotes repair of damaged endothelium. This happens due to the concomitant expansion of a Tang subset with immunosenescent features, including the loss of CD28. Therefore, the aim of this study was to elucidate the interplay between Tang subpopulations and endothelial cells in a group of young SLE patients without previous cardiovascular events. Twenty SLE female patients aged less than 40 years and 10 healthy controls (HCs) were recruited. Serum levels of interleukin (IL) -6, -8, matrix metalloproteinase (MMP) -9 and interferon (IFN) -γ were measured and flow cytometric analysis of endothelial progenitor cells (EPCs) and Tang subsets were performed. Human umbilical vein endothelial cells (HUVECs) proliferation and pro-inflammatory phenotype in response to subjects’ serum stimulation were also evaluated. Results showed that the percentage of Tang and EPCs subsets was reduced in SLE patients compared with HCs, with a marked increase of senescent CD28null cells among Tang subset. Furthermore, IL-8 serum levels were directly correlated with the percentage of Tang and inversely related to the CD28null Tang subsets, SLE disease activity index -2000 (SLEDAI-2K) was inversed related to Tang cells percentage. We indirectly evaluated the role of the Tang subset on the endothelium upon stimulation with serum from subjects with a low percentage of Tang CD3+ cells in HUVECs. HUVECs displayed pro-inflammatory phenotype with up-regulation of mRNA for IL-6, intercellular adhesion molecule (ICAM) -1, endothelial leukocyte adhesion molecule (ELAM) -1; cell proliferation rate was directly related to IL-8 serum levels and EPCs percentage. In highly selected young SLE patients without previous CV events, we found that the deterioration of Tang compartment is an early event in disease course, preceding the development of an overt cardiovascular disease and potentially mediated by SLE-specific mechanisms. The overcome of the CD28null subset exerts detrimental role over the Tang phenotype, where Tang could exert an anti-inflammatory effect on endothelial cells and might orchestrate via IL-8 the function of EPCs, ultimately modulating endothelial proliferation rate.